Neoadjuvant Stereotactic Radiotherapy for Brain Metastases - Talapatra, Kaustav; Balakrishnan, Rajesh; Gupte, Ajinkya (Indian Journal of Medical and Paediatric Oncology, 2025)
Brain metastases occur in ∼10% of cancer patients, with rising incidence due to improved diagnostic imaging and advances in systemic therapies. Managing these metastases remains challenging, as they are associated with significant morbidity and mortality. Standard treatment approaches include surgical resection followed by whole-brain radiation therapy or focused radiation techniques such as stereotactic radiosurgery. While whole-brain radiation therapy offers excellent regional control, it is linked with long-term cognitive decline, leading to a shift toward more localized radiation strategies.Delivering radiation before surgery, known as neoadjuvant stereotactic radiosurgery, has emerged as a promising approach with several potential advantages. Administering radiation to intact tumors ensures better oxygenation, enhancing the effectiveness of radiation. This approach may also reduce the risk of cancer cell dissemination during surgery by treating the tumor beforehand, lowering the chances of leptomeningeal spread. Additionally, intact tumors are easier to outline on imaging, improving the accuracy of radiation delivery and minimizing exposure to surrounding healthy brain tissue.Preliminary studies indicate that neoadjuvant stereotactic radiosurgery offers comparable outcomes in terms of local control and survival when compared with postoperative radiation. Some evidence also suggests reduced rates of leptomeningeal disease and radiation-related complications. However, challenges remain, including the lack of histopathological confirmation of malignancy before treatment, raising concerns about misdiagnosis. Further clinical trials are needed to establish the safety, efficacy, and optimal use of this approach.This review explores the evolving role of neoadjuvant stereotactic radiosurgery for brain metastases, discussing its potential benefits, limitations, and future research directions.
Keywords: neoadjuvant; preoperative; stereotactic radiotherapy